2020
DOI: 10.3389/fsurg.2020.598728
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Lift as a Safe and Effective Procedure for Prostatic Hyplasia Population: A Systematic Review and Meta-Analysis

Abstract: Background: Prostatic urethral lift (PUL) is a relatively new minimally invasive treatment procedure for benign prostatic hyperplasia (BPH). In order to analyze the sustainability of this new protocol, a systematic review and meta-analysis is performed based on the published articles.Methods: We performed a critical review according to the preferred reporting items for systematic review and meta-analysis (PRISMA) and MOOSE guidelines. A total of 818 published articles matched our search terms, and 11 studies m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We identified several systematic reviews focusing on MITs, reporting similar findings concerning the efficacy of TIND, PUL, PAE and WVTT, and highlighting that these are relatively effective treatments, with a lower incidence of adverse events and sexual dysfunction, compared to TURP [73][74][75][76][77][78]. While some of these findings are similar to those of the present review, we highlight the uncertainty surrounding some of these outcomes, especially those related to sexual function, in which the data are sparse and usually available for only a subset of participants in each study, as was highlighted by one review [79].…”
Section: Discussionmentioning
confidence: 94%
“…We identified several systematic reviews focusing on MITs, reporting similar findings concerning the efficacy of TIND, PUL, PAE and WVTT, and highlighting that these are relatively effective treatments, with a lower incidence of adverse events and sexual dysfunction, compared to TURP [73][74][75][76][77][78]. While some of these findings are similar to those of the present review, we highlight the uncertainty surrounding some of these outcomes, especially those related to sexual function, in which the data are sparse and usually available for only a subset of participants in each study, as was highlighted by one review [79].…”
Section: Discussionmentioning
confidence: 94%
“…However, there are discrepancies regarding the effectiveness of PAE and PUL when compared with TURP. These are largely attributed to variability in the studies included in the meta‐analyses, since some used both non‐randomized trials and RCTs due to the scarcity of RCTs published [36,37,40]. This may have introduced a bias in their results, which should therefore be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The greater improvement of objective outcomes in TURP can own resective procedures remove greater amount of prostatic tissue creating a wider‐open prostatic fossa, and consequently a greater relief of BOO [35]. Recent meta‐analyses have also demonstrated that TURP produces better improvements in most patient outcomes compared with PAE [36–39] and PUL [35,40,41]. However, there are discrepancies regarding the effectiveness of PAE and PUL when compared with TURP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation